Acute myocarditis as the main clinical manifestation of SARS-CoV 2 infection: A case report - Gianluca Cuomo; Marianna Menozzi; Federica Carli; Margherita Digaetano; Alessandro Raimondi; Letizia Reggianini; Guido Ligabue; Giovanni Guaraldi; Cristina Mussini (MDPI AG, 2020)
We describe a case of acute myocarditis which was reported as the main COVID-19 clinical manifes-tation, with a favorable outcome. In addition to symptoms, laboratory tests (BNP and troponin), echo-cardiogram and cardiac MRI contributed to diagnosis. Regardless heart biopsy was not obtained, it is likely an immunological pathogenesis of this condition which pave the way to further therapeutic im-plications, since there are currently no standardized treatments.